AVALIAÇÃO DO USO DE PLANILHAS COMPUTACIONAIS COMO UMA FERRAMENTA DIDÁTICA EM QUÍMICA ANALÍTICA QUALITATIVA - Denari,Gabriela B. (2016)
The use of spreadsheet softwares is not widespread in Chemical Education in Brazil as a computational education tool. By its turn the Qualitative Analytical Chemistry is considered a discipline with classical and non-flexible content. Thus in this work the spreadsheet software Excel® was evaluated as a teaching tool in a Qualitative Analytical Chemistry course for calculations of concentrations of the species in equilibrium in solutions of acids. After presenting the theory involved in such calculations the students were invited to elaborate the representation of the distribution of these species in a graphical form, using the spreadsheet software. Then the teaching team evaluated the resulting graphics regarding form and contents. The graphics with conceptual and/or formal errors were returned for correction, revealing significant improvement in the second presentation in all cases. The software showed to be motivating for the content of the discipline, improving the learning interest, while it was possible to prove that even in classical disciplines it is possible to introduce new technologies to help the teaching process.